ANALYTICAL STUDY ON THE DEVELOPMENT OF METHODS IN LEARNING ARABIC LANGUAGE - Ana Sofia (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2023)
The application of the Arabic language learning method that has been developed still focuses on the approachable grammar method. This is evident from the special characteristics that have been developed. The aim of this research is to analyze the development of methods in learning Arabic. The research method in this research is a literature study. This paper uses three types of source materials, namely: primary, secondary and tertiary. The analytical technique applies three analytical techniques: deductive, inductive and comparative. The research results show that Arabic language learning has experienced development and evolution in methods over the last few decades. Various factors, such as technological developments, research in linguistics, and better understanding of the language learning process, have contributed to this progress. The following are several methods that are generally used in learning Arabic and its development: 1). Grammar-Translation Method, 2). Direct Method (Communication Oriented), 3). Task Based Method, 4). Technology Based Methods, 5). Project Based Method and 6). Skills Integrated Learning (Integrated Skills Approach). So, using a combination of methods that suit student needs and learning objectives can provide better results. In addition, a contextual-based approach, direct experience, and practical application help increase the effectiveness of Arabic language learning.